On the Internet of Things, Blockchain Technology for Supply Chain Management (IoT). (10th May 2022) - Sharma, Viresh; Ramirez-Asis, Edwin; Ahmad, Aamir Junaid; Silva-Zapata, Miguel; Alvarado-Tolentino, Joseph; Kumar, Harish; Krah, Daniel
Abstract : Patient's medical records are now accessible from anywhere and at any time, thanks to the Internet and the changes it has wrought in the healthcare industry. Electronic health records were dogged by a lack of standards, but that was not the only issue. Decentralized online ledgers were already being proposed and used to solve interoperability and privacy issues when blockchain-based systems were first built. As far as technical issues go, scaling, usability, and accessibility stand out. On the one hand, it is difficult to keep secure access control measures on-chain while simultaneously keeping a wide range of medical data off-chain. Finding out who owns what and spreading access control of data is the second challenge in medical settings. Using temporal blockchain, the Secured Healthcare System (SHS) aims to address these problems (TB). As an SHS fundamental building piece, the context-based Merkle tree emphasizes privacy, enhanced integrity management, and access control methods (CBMT). For interoperability and scale control, the framework uses temporal features, HL7 criteria, and IPFS data management (IPFS). Personalized micro booklet (PML) security was found to be affected by the SHS framework, namely, on the time-based shadow notions and the contextual components of the PML (PML). Taking advantage of the architecture's enormous potential to solve the challenges of siloed data and enabling tamper-proof, secure healthcare transaction has been sought.